Semantic Relationships in the Interpretation of the Steps of Contemplation and the Minutes of Contemplation by Abd al-Rahman al-Maidani (1425 AH - Mustafa Sabah Mhodar / Anjerais Tuama Youssef ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The Holy Qur’an constitutes the broadest field from which scholars draw their topics. Because of its miraculous importance that no other text has, the linguist, jurist, fundamentalist, and rhetorician dealt with it to understand its meanings and discover the secrets of its miraculousness. The goal of the research was to find out some of the semantic relationships for the interpretation of (Marage AlTafakir fe Dacakc Al Tadaber of Contemplation and the Minutes of Contemplation), by Sheikh Abd al-Rahman al-Maidani (d. 1425 AH), who It falls within the standard of textual plotting in textual linguistics, as it relied on many semantic relationships in interpreting and clarifying the Book of God Almighty. The research plan required that it be divided into an introduction and three sections, which dealt with the introduction, the definition of semantic relationships, the life of the interpreter and its scientific effects, and the definition of interpretation. The first section dealt with the relationship of gradualism, while the second section dealt with the relationship of causality. The third section dealt with the relationship of generality and detail, in accordance with what the Qur’anic discourse requires, highlighting the most important results reached by the researcher, and presenting a list of the sources and references on which he relied.